2010
DOI: 10.1007/s00418-010-0718-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury induces cholesterol 24-hydroxylase (Cyp46) expression in glial cells in a time-dependent manner

Abstract: Maintaining the cholesterol homeostasis is essential for normal CNS functioning. The enzyme responsible for elimination of cholesterol excess from the brain is cholesterol 24-hydroxylase (Cyp46). Since cholesterol homeostasis is disrupted following brain injury, in this study we examined the effect of right sensorimotor cortex suction ablation on cellular and temporal pattern of Cyp46 expression in the rat brain. Increased expression of Cyp46 at the lesion site at all post injury time points (2, 7, 14, 28 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…CYP46A1 expression would be an adaptive response of the retina to changes in cholesterol levels. Similar activation of CYP46A1 in microglia was already reported in the brain in response to injury (Smiljanic et al, 2010).…”
Section: Cholesterol-24s-hydroxylase 24s-hydroxycholesterol and Neursupporting
confidence: 84%
“…CYP46A1 expression would be an adaptive response of the retina to changes in cholesterol levels. Similar activation of CYP46A1 in microglia was already reported in the brain in response to injury (Smiljanic et al, 2010).…”
Section: Cholesterol-24s-hydroxylase 24s-hydroxycholesterol and Neursupporting
confidence: 84%
“…Previously, we and others have shown that activated macrophages/microglia express CYP46A1 in traumatic brain injury 26, 46 . Additionally, it was suggested that infiltrating macrophages express CYP46A1 during EAE 45 .…”
Section: Discussionmentioning
confidence: 80%
“…CYP46A1 expression was found in many types of neurons, where a majority of CYP46A1 expression was exclusively associated to neuronal somata, with lower levels found in dendrites 23, 26, 44, 56 . This study also revealed a strong CYP46A1 immunoreactivity in the neuronal somata in the grey matter at the onset and the end of EAE, which was lowered at the peak of disease probably due to neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As so far only few studies demonstrated atypical Cyp46 expression in astrocytes under certain circumstances [e.g. human frontal cortex- (Brown et al 2004), and advanced Alzheimer disease- (Bogdanovic et al 2001)], Smiljanic et al (2010) were interested to study cellular and temporal pattern of Cyp46 expression in the context of traumatic brain injury (TBI), a widespread cause of death and major source of adult disability. Employing a rat TBI model the authors found longlasting neuronal and glial Cyp46 expression at the lesion site, indicating that TBI-induced production of damaged cell membranes elicits wide-spead Cyp46 expression to re-establish brain cholesterol homeostasis required for a glial scar formation.…”
Section: Central Nervous Systemmentioning
confidence: 99%